A new heavy tailed class of distributions which includes the Pareto - Deepesh Bhati; Enrique Calderín-Ojeda; Mareeswaran Meenakshi (Risks, 2019)
In this paper, a new heavy-tailed distribution, the mixture Pareto-loggamma distribution, derived through an exponential transformation of the generalized Lindley distribution is introduced. The resulting model is expressed as a convex sum of the classical Pareto and a special case of the loggamma distribution. A comprehensive exploration of its statistical properties and theoretical results related to insurance are provided. Estimation is performed by using the method of log-moments and maximum likelihood. Also, as the modal value of this distribution is expressed in closed-form, composite parametric models are easily obtained by a mode matching procedure. The performance of both the mixture Pareto-loggamma distribution and composite models are tested by employing different claims datasets.
Keywords: 330; composite models; excess-of-loss reinsurance; loggamma distribution; pareto distribution